Measurements of the flight trajectory of a spinning soccer ball and the magnus force acting on it - Asai, T.; Kimachi, K.; Liu, R.; Koido, M.; Nakayama, M.; Goff, J. E.; Hong, S. (Proceedings, 2020)
The trajectory of a soccer ball, kicked with a spin to curve it into the goal, is strongly influenced by aerodynamic factors such as the Magnus force. Several studies using a wind-tunnel and high-speed cameras have investigated the Magnus force acting on a spinning soccer ball. However, the exact effect of the Magnus force on the trajectory of a spinning soccer ball in free flight remains unclear. This study set out to use an optical three-dimensional motion-capture system to record the details of the flight of such a spinning soccer ball. The maximum curvature of the ball`s trajectory occurred in the middle of its flight. The sideways-directed Magnus force acting on the ball decreased as the ball`s speed decreased during the entire flight. Thus, it was concluded that the deflection of the trajectory of the ball decreases as the sideways-acting force decreases throughout the flight.